Developing English Material in the Form of Digital Flipbook as a Medium for Teaching English - Andi Tenrisanna Syam; Dina Mahriati; Magfirah Thayyib; Yuyun Ruqiyyat Said; Fadhliyah R. Muin (Universitas Islam Negeri Palopo, 2025)
This research aims to develop English material in the form of a digital flipbook as a medium for teaching English. This research used the research and development (R&D) method and adopted the 4-D model. The research participants were seventh-grade English teachers and 60 SMP Negeri 3 Wotu students. The needs of teachers and students were analyzed through interviews and questionnaires, which use quantitative and qualitative data analysis techniques. The result of the need analysis showed that the English material needs to be developed. The mean score obtained from the three judges of the flipbook-based English language material is 4.5, categorized as